Politics of Force : Bargaining during International Crises - Young, Oran R. (Book collections on Project MUSE., 2015)
Examining the Berlin crises of 1948-49 and 1961, the Taiwan Strait crisis of 1958, and the Cuban crisis of 1962, the author elucidates various intermediate and highly politicized forms of international coercion.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.